Capital mobility and financial integration : a survey - Kenen, Peter B. (Princeton, N.J. : International Finance Section, Dept. of Economics, Princeton University, 1976)
This book examines the evolution of policies, markets, and financial institutions in major countries. The subject has several dimensions, real and monetary, positive and normative, short and long term. The international integration of financial markets, the relationships between mobility and integration were also examined.
Includes bibliography p. 73-78.
usc 16/08/2018
Loans
Keywords: Capital movements; International finance; Balance of payments; Fiscal policy; Monetary policy